BrainPhys Neuronal Media Support Physiological Function of Mitochondria in Mouse Primary Neuronal Cultures - Faria-Pereira, Andreia; Temido-Ferreira, Mariana; Morais, Vanessa A. (Frontiers in Molecular Neuroscience, 2022)
In vitro neuronal cultures are extensively used in the field of neurosciences as they represent an accessible experimental tool for neuronal genetic manipulation, time-lapse imaging, and drug screening. Optimizing the cultivation of rodent primary neuronal cultures led to the development of defined media that support the growth and maintenance of different neuronal types. Recently, a new neuronal medium, BrainPhys (BP), was formulated envisioning the mimicry of brain physiological conditions and suitability for cultured human iPSC-derived neurons and rat primary neurons. However, its advantages in mouse primary neuronal cultures and its effects in neuronal bioenergetics are yet to be demonstrated. In this study, we validated the beneficial use of BP in mouse primary neuronal cultures based on the observation that neuronal cultures in BP media showed enhanced ATP levels, which increased throughout neuronal maturation, a finding that correlates with higher mitochondrial activity and ATP production at later maturation stages, as well as an increased glycolysis response on mitochondrial inhibition and increased mitochondrial fuel flexibility. Taken together, our data demonstrate that BP medium promotes mitochondrial activity along with neuronal maturation of in vitro cultures.